The non-linear impacts of crude oil prices and trade openness on the foreign income of Bangladesh - Parvin, Rehana; Rahman, Md Lutfar (IUBAT Review, 2023)
A Market based study was conducted in the high (Tanore Upazila) and low (Natore Upazila) drought prone areas over the period of twelve months with the aims to know the impacts of drought on the market. Drought inhibits production, the inflow of agricultural produces and food supply in high drought market areas. Availability, diversity, price and sources of plant species become more restricted by the severe drought. The high drought market area shows less availability of the produces with low diversity and high prices. These attributes arrest consumer’s behavior in food consumption patterns and restricted food supply in high drought market. Low drought market area shows normal production, regular inflows of agricultural produces. Mostly drought affects market in the Kharif-2 season. More local varieties were found in the low drought market during Rabi season. Appropriate drought forecasting in advance and drought insurance can protect production loss and ensure market supply. IUBAT Review—A Multidisciplinary Academic Journal, 6 (1): 61-76